Estimating Costs Associated with Adverse Events in Patients with Advanced Lung Cancer - Lin CY; Wu TI; Yang SC (ClinicoEconomics and Outcomes Research)
Chien-Yu Lin,1 Tzu-I Wu,1,2 Szu-Chun Yang1 1Division of Thoracic Medicine, Department of Internal Medicine, National Cheng Kung University Hospital, College of Medicine, National Cheng Kung University, Tainan, Taiwan; 2Department of Public Health, College of Medicine, National Cheng Kung University, Tainan, TaiwanCorrespondence: Szu-Chun Yang, Email yangszuchun@gmail.comPurpose: This study aimed to estimate the costs associated with adverse events (AEs) in advanced lung cancer patients treated with first-line therapies.Subjects and Methods: All patients with advanced lung cancer diagnosed between 2011 and 2019 were identified from the Taiwan National Cancer Registry. First-line treatment was defined as a therapy that began within 30 days before and 90 days after the diagnosis. We defined a newly-developed AE as one established after first-line treatment had commenced, with the contingency that the patient had not been diagnosed with the AE within one year prior to the outset of therapy. One patient with a specific AE was matched on age, sex, and regimens with four patients without the AE. Payments incurred over the same period of time in the two groups were compared to estimate the AE-related costs.Results: A total of 27,376 patients receiving first-line targeted therapy, immunotherapy, or chemotherapy were identified. Clinical characteristics of 15,454 treatment episodes with a specific AE and 61,816 treatment episodes without the AE were well balanced. The costliest AEs of any severity were sepsis/septicemia, neuropathy, and acute kidney injury, with the respective average incremental costs of 10101, 9982, and 7839 USD. The costliest severe AEs requiring hospitalization were sepsis/septicemia, interstitial lung disease/pneumonitis, and neuropathy, with mean incremental costs of 22483, 10645, and 10120 USD, respectively.Conclusion: Costs associated with AEs in advanced lung cancer patients treated with first-line therapies were substantial. These estimates could be adopted for future cost-effectiveness analyses of new lung cancer treatments.Keywords: adverse event, side effect, cost, lung cancer, utilization